Pengambilalihan Flight Information Region (FIR) Singapura Atas Kepulauan Riau Dan Natuna - Drajat, Harwita Sari (Universitas Jayabaya, 2023)
The existence of an FIR between Singapore and Indonesia should strengthen sovereignty by prioritizing national interests. However, this was not achieved. This prompted the author to conduct research with the aim of analyzing the position of Presidential Regulation Number 109 of 2022 concerning Ratification of the Agreement Between the Government of the Republic of Indonesia and the Government of the Republic of Singapore Regarding the Adjustment of Boundaries Between the Flight Information Region of Jakarta and the Flight Information Region of Singapore Regarding the Implementation of the Flight Information Region (FIR) as well as analyzing the position of Indonesian sovereignty after the takeover of Singapore's FIR by Indonesia with the issuance of Presidential Regulation Number 109 of 2022 concerning Ratification of the Agreement between the Government of the Republic of Indonesia and the Government of the Republic of Singapore Regarding Boundary Adjustments between the Jakarta Flight Information Region and the Singapore Flight Information Region. The approach method uses normative juridical. The data collection technique that will be used in this research is document study. The data analysis method is normative qualitative. The conclusion that can be obtained based on the results of the analysis is that it does not indicate a complete and complete takeover of Indonesia's air space as mandated in Article 458 of Law Number 1 of 2009, which will be taken over in 2024. Apart from that, it becomes stronger with the existence of the takeover scheme being carried out. guided by the national interests of Indonesian sovereignty. This indicates that Presidential Regulation Number 109 of 2022 concerning Ratification of the Agreement Between the Government of the Republic of Indonesia and the Government of the Republic of Singapore Regarding Boundary Adjustments Between the Flight Information Region of Jakarta and the Flight Information Region of Singapore has a position to strengthen the schematization of national interests, both in terms of sovereignty and national resilience. as well as the economy so that Indonesia's sovereignty is strong